Galaxy and Mass Assembly (GAMA): Low-redshift Quasars and Inactive Galaxies Have Similar Neighbors - Stone Maria B; Wethers Clare F; de Propris Roberto; Kotilainen Jari; Acharya Nischal; Holwerda Benne W; Loveday Jonathan; Phillipps Steven (IOP Publishing Ltd, 2025)
We explore the properties of galaxies in the proximity (within a similar to 2 Mpc radius sphere) of Type I quasars at 0.1 <0.35, to check whether and how an active galaxy influences the properties of its neighbors. We further compare these with the properties of neighbors around inactive galaxies of the same mass and redshift within the same volume of space, using the Galaxy and Mass Assembly spectroscopic survey. Our observations reveal no significant difference in properties such as the number of neighbors, morphologies, stellar mass, star formation rates, and star formation history between the neighbors of quasars and those of the comparison sample. This implies that quasar activity in a host galaxy does not significantly affect its neighbors (e.g., via interactions with the jets). Our results suggest that quasar host galaxies do not strongly differ from the average galaxy within the specified mass and redshift range. Additionally, the implication of the relatively minor importance of the environmental effect on and from quasars is that nuclear activity is more likely triggered by internal and secular processes.